The approach to formation of the competence component structure - Efim L. Kon; Vladimir I. Freyman; Aleksandr A. Yuzhakov; Ekaterina M. Kon (Высшее образование в России)
This article focuses on the methodical solutions for formation of the basic educational programs, which are constructed on the Federal state educational standards of the third generation. In particular, there are given the recommendations concerning the structuring of the competences component elements, and also about the selection of the most effective method of their creation, checking and assessment.